2018
DOI: 10.21873/anticanres.12509
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell-selective Synergism of TRAIL- and ATRA-induced Cytotoxicity in Breast Cancer Cells

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The IC 50 value of rhTRAIL in each of the cell lines was calculated using a linear regression formula ( y = m x + c) from a scatter plot, whereby the x -axis was the concentration of TRAIL (in log10), y was the percentage of cell viability, m was the gradient, and c was the y -intercept value. The IC 50 value of TRAIL was then calculated by anti-log of the derived TRAIL concentration value (in log10) from 50% of cell viability [138,139].…”
Section: Methodsmentioning
confidence: 99%
“…The IC 50 value of rhTRAIL in each of the cell lines was calculated using a linear regression formula ( y = m x + c) from a scatter plot, whereby the x -axis was the concentration of TRAIL (in log10), y was the percentage of cell viability, m was the gradient, and c was the y -intercept value. The IC 50 value of TRAIL was then calculated by anti-log of the derived TRAIL concentration value (in log10) from 50% of cell viability [138,139].…”
Section: Methodsmentioning
confidence: 99%
“…β-carotene also enhances the apoptosis of breast cancer cells by enhancing the activation of caspase 3 [ 159 ]. A combination of vitamin A with a chemotherapy drug or pro-apoptotic molecules potentiates breast cancer cell death by decreasing pro-survival Bcl-2, increasing pro-death Bax, and activating caspases [ 160 , 161 , 162 ]. CTCs isolated from breast cancer patients demonstrate an altered apoptotic pathway [ 91 , 92 ], and FSS exposed breast cancer cells decrease the abundance of pro-apoptotic proteins such as caspase 3 [ 29 , 52 ].…”
Section: Antioxidant and Breast Cancer Metastasismentioning
confidence: 99%
“…The dual effects of common chemotherapies in cancer, either as a cytotoxic drug or as a sensitizer to the effect of TRAIL and MSC-TRAIL have also been demonstrated in several tumor xenografts including those of brain cancer [ 40 ], hepatocellular carcinoma [ 41 ], breast cancer [ 42 ] and NSCLC [ 43 ]. Furthermore, TRAIL and MSC-TRAIL either alone or in combination with other chemotherapies have also been shown to be effective in targeting CSCs in breast [ 44 , 45 ] and liver cancer [ 46 ]. Although we have found that MSC-TRAIL was effective in targeting the cell lines and their CSCs, one out of the three NSCLC cell lines used was TRAIL-resistant [ 47 ].…”
Section: Introductionmentioning
confidence: 99%